Rethinking management accounting education: a study on innovative teaching approaches and student perceptions - Jamaluddin, Sabariah; Mat Bahari, Anis Barieyah; Mustafa, Lily Mazlifa; Wan Abdul Rahman, Nor Hawani; M. Yacob, Noor Hasimah; Mohammad Fadzillah, Nur Syazwani (GADING Journal for the Social Sciences, 2025)
Management accounting can be one of the toughest courses for undergraduate accounting students, with traditional teaching methods like “chalk and talk” often falling short. Students today need more practical skills to succeed in their careers, and innovative learning tools can help fill this gap. This study focuses on students’ perceptions of learning Job and Batch Costing topic using Cost-It-Right System. The feedback from Part Two Diploma in Accountancy students at UiTM Pahang was collected through an online survey. The results showed that 83% of students preferred using innovative tools to learn this topic. On top of that, their ratings for interest and preference ranged from 3.77 to 4.19 out of 5, which indicate positive views on these learning tools. Overall, the study highlights a strong preference for innovative teaching methods in management accounting, and it is hoped that these insights will help educators create more engaging and practical learning experiences for students.